Journalling (Assemble You, 2024)
Welcome to Audio Learning from Assemble You. Join us for a valuable lesson on the art and impact of journalling. This session takes a deep dive into how the simple act of writing your thoughts and experiences can become a powerful tool for personal and professional growth. Through engaging stories and practical tips, we'll explore how journalling can help you navigate work challenges, improve decision-making, and enhance your leadership skills. Whether you're a seasoned writer or a complete beginner, our insightful advice and easy-to-follow guidelines will help you to harness the benefits of journalling. So, let's journey together and discover how these written reflections can become your secret weapon to overcoming obstacles and thriving in your career. Learning Objectives Discover and appreciate the concept of journalling, recognising its significance as a personal development tool and a mechanism for professional growth. Gain practical insights and strategies on how to embark on the journalling journey. Acknowledge and overcome common barriers to journalling, such as writer's block, distractions and time management issues.
Online resource; title from title details screen (O'Reilly, viewed January 17, 2024)
Keywords: Diaries; Journaux intimes; Art d'écrire; Journaux intimes; Emploi en thérapeutique; Audiobooks; Livres audio